Estimative of royalties: appropriation of gains provided by innovations associated with plant breeding (Research, Society and Development, 2021)
Genetic breeding is based on the inheritance of quantitative traits, which provides the basis for developing methods that can be used to increase the rate of genetic improvement, known as genetic gain. Through selection, new varieties of plants can be obtained, which can be protected. Thus, this research investigates the mechanisms for estimating royalties in protected cultivars and the importance of genetic gains in such estimations. A systematic review was carried out based on articles published in 10 years, from 2009 to 2019, in the scientific bases Scopus (71) and Web of Science (73). The main crop, take as an example, was sugar cane. A survey of documents was carried out containing the Boolean terms and operators: “(genetic * and gain) and (sugarcane or cane)” in the title and/or abstract. One hundred forty-four articles were searched. After processing the data and removing duplicate documents, 107 scientific articles remained. With an average publication of 6.38 publications per year. Average of 14.6 citations per document. There were 463 authors and 456 co-authors, with nine documents having single authorship and an average of 4.33 authors per article. After the refinement process, a study sample of 25 articles was obtained. The analyzed journals provided information about the estimates, applied model, and study variables, being of great importance in constructing a linear regression model of royalty valuation linked to intellectual property rights related to the breeder of plant breeding.